Priority directions of development of science and education – 2025 - Комісаренко, Алла Григорівна; Михальська, Світлана Іванівна; Кривошеєв, Ігор Віталійович; Гудзь, Петро Васильович; Подаков, Євгеній Сергійович; Олексюк, Ярослав Ростиславович; Туваєва, Анна Юріївна; Онищенко, Сергій Вікторович; Глухманюк, Сергій Олександрович; Бурчак, Ліана Володимирівна; Денисенко, Людмила Іванівна; Дмитрієва, Світлана Михайлівна; et al. (DEL c.z., 2025)
The collection includes materials of the VII International research and practical internet conference "Priority directions of development of science and education". The materials of the collection will be useful for researchers, scientists, graduate students, researchers, teachers, students